(3GdNWH GdfHGJjIs - (3YHO GdQMje Hf eMeO Hf ESeGYjd GHf fHGJI GdaGQbj, CHhjMji,J (B374 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN GdZfhi GdQbi bQGAI Ydjg ai SfI CQHY hYTQjf hNeSeGFI , bGd CNHQfG GHf fHGJI NWHI jPcQ ajgG GSJbHGd GdSfI haVd jhe YGThQG s
(3BNQgG (B:s
(3Chd gPg GdNWHI GdeHJhQI (B: (3GdMeO ddg GdcQje Whdg GdYXje Uhdg GdeQghH YOdg GdeWdhH aVdg hZQGHjH eYWha Ydi HjV ChYg LOO cCfg bjd hef GdLHGd s
(3QhGjI CHh ESMGb EHQGgje Hf eMeO Hf fHgGf GdZfhi GdQbis
(3HBNQgG SeGY Ydi GdTjN YdGA GdOjf CHh GdMSf Ydi Hf Ydi Hf eSeGQ GdeYQha HGHf GdUjQai JGQjNg SfI (B736s
(3Ke Jedc (B809 (3hHChdgG Jedc SfI (B775s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B347 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B211s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs